CFD investigation of mechanical heart valve orientations in modulating left ventricular hemodynamics - R.S.V.N. Murty; P. Pabsetti; R. Harish (Results in Engineering)
This study provides a comprehensive computational analysis of how mechanical heart valve orientations impact left ventricular (LV) hemodynamics, with potential implications for surgical valve placement. Focusing on monoleaflet valves (MLV) and bileaflet valves (BLV), the research explores how different valve angles influence blood flow patterns within the LV chamber. The analysis includes velocity contours, streamline patterns, vorticity contours, and temporal velocity fluctuations to elucidate the effects of valve orientation on LV performance. Findings indicate that valve orientation significantly influences flow coherence and blood velocity. For instance, a 20-degree orientation in the MLV alters jet flow in ways that could affect wall shear stress distribution. At a 45-degree angle, the MLV produces a more centralized jet flow, enhancing flow uniformity and aligning more closely with physiological conditions. In contrast, a 55-degree angle skews the jet flow, potentially leading to adverse hemodynamic effects. Similarly, BLV orientations at 45, 55, 60, and 70° showed that lower angles improved flow efficiency, reducing energy losses and minimizing the risk of regurgitation, while higher angles led to turbulent and potentially damaging flow patterns. Comparative results at a 45-degree orientation demonstrated the superior performance of BLV in regulating normal velocity, with BLV reducing average blood velocity by 38.77 % compared to a 29.53 % reduction with MLV. These results underscore the importance of optimizing mechanical heart valve orientations to enhance left ventricular hemodynamics. The findings carry significant clinical implications, supporting evidence-based valve placement decisions that can substantially improve patient outcomes, survival rates and long-term cardiovascular health.